Efficacy of different insecticides against cotton leafhoppers (Amrasca Biguttula Biguttula (Ishida)) In RCH-2 BG-II. - T. RAMESH BABU, B. DILEEP KUMAR, D. SRIDEVI and (The Journal of Research, PJTSAU, 2017)
Among the sucking pests attacking cotton, leafhoppers (Amrasca biguttula biguttula (Ishida)) are very important. SevenÂ different insecticides viz., imidacloprid 70% WG, fipronil 80% WG, diafenthiuron 50% WP, buprofezin 25% SC, acephate 75% SP,acetamiprid 20% SP, imidacloprid 17.8% SL were evaluated against leafhoppers in RCH-2 BG-II cotton hybrid during kharif 2011- 12 and 2012-13. Diafenthiuron was the most effective insecticide with 77.84 per cent reduction of leafhoppers population withÂ highest yield(2227 kg ha-1) followed by imidacloprid 70% WG, fipronil , buprofezin and acephate .